2004
DOI: 10.1097/01.sla.0000143300.49878.51
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Dihydropyrimidine Dehydrogenase in Adjuvant 5-Fluorouracil Liver Perfusion Chemotherapy for Pancreatic Cancer

Abstract: An immunohistochemical evaluation of intratumoral DPD expression might be useful in predicting responsiveness to 5-FU-based chemotherapy in pancreatic cancer patients. In the DPD(-) group, liver perfusion chemotherapy using 5-FU via the portal vein is effective adjuvant therapy for pancreatic cancer once pancreatectomy has been performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
25
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 20 publications
4
25
0
Order By: Relevance
“…However, the postoperative survival period in patients treated with 5-FU through the portal vein for 2 weeks was still limited, and thus, these results were unsatisfactory. In a strategy similar to ours, Nakayama et al [13] continuously infused 250 mg/day of 5-FU via the portal vein for 3 weeks immediately after radical surgery in pancreatic cancer patients. As a result, patients who received 5-FU liver perfusion chemotherapy, especially those with negative expression of dihydropyrimidine dehydrogenase in the tumors, showed a significantly higher survival rate than those without the therapy.…”
Section: Discussionmentioning
confidence: 99%
“…However, the postoperative survival period in patients treated with 5-FU through the portal vein for 2 weeks was still limited, and thus, these results were unsatisfactory. In a strategy similar to ours, Nakayama et al [13] continuously infused 250 mg/day of 5-FU via the portal vein for 3 weeks immediately after radical surgery in pancreatic cancer patients. As a result, patients who received 5-FU liver perfusion chemotherapy, especially those with negative expression of dihydropyrimidine dehydrogenase in the tumors, showed a significantly higher survival rate than those without the therapy.…”
Section: Discussionmentioning
confidence: 99%
“…An immunohistochemical evaluation of DPD expression in 68 pancreatic tumors revealed that in the DPD low-expression group the adjuvant 5-FU chemotherapy subgroup showed a significantly higher survival rate than the untreated subgroup. Moreover, among the treated patients, OS was significantly better in the DPD-negative subgroup than in the DPD-positive subgroup (49). Similarly, a recent study showed that high TS immunoreactivity, detected in 43% and 47% of the primary and metastatic lesions, respectively, had a significant influence on the outcome of patients with resectable pancreatic cancer, and the rate of survival of the high TS group was significantly higher than that of the negative or low reactivity groups.…”
Section: Molecular Determinants Related To Drug Sensitivitymentioning
confidence: 91%
“…In addition, more efforts could be focused on controlling liver metastasis to avoid hepatic failure. In this regard, IORT combined with liver perfusion chemotherapy could be one of the most reasonable treatment options in cases of liver metastasis [28,33]. …”
Section: Discussionmentioning
confidence: 99%